2020
DOI: 10.25046/aj050243
|View full text |Cite
|
Sign up to set email alerts
|

Extending Movable Surfaces with Touch Interaction Using the VirtualTablet: An Extended View

Abstract: Immersive output and natural input are two core aspects of a virtual reality experience. Current systems are frequently operated by a controller or gesture-based approach. However, these techniques are either very accurate but require an effort to learn, or very natural but miss haptic feedback for optimal precision. We transfer ubiquitous touch interaction with haptic feedback into a virtual environment. To validate the performance of our implementation, we performed a user study with 28 participants. As the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Feedback can be used as a reminder of movements in different parts, and studies have found that tactile sensation improves user engagement [9]. In [10], the author described the evaluation of human-computer interaction with the decision-making model. The information flow is helpful to monitor the effectiveness of the collective's activities.…”
Section: Introductionmentioning
confidence: 99%
“…Feedback can be used as a reminder of movements in different parts, and studies have found that tactile sensation improves user engagement [9]. In [10], the author described the evaluation of human-computer interaction with the decision-making model. The information flow is helpful to monitor the effectiveness of the collective's activities.…”
Section: Introductionmentioning
confidence: 99%